Identifying Key Risk Factors for Incisional Hernia Post-Emergency Laparotomy: Insights from A Case-Control Study from a Tertiary Referral Center of Eastern India. - Ansari, Reyaz; Manna, Saurav; Halder, Dibakar; DE, UTPAL (International Journal of Medical Students, 2025)
BACKGROUND: Incisional hernias (IH) are gaps around postoperative scars, detectable by examination or imaging, with variable incidence. Despite surgical advancements, IH remains a significant complication, causing morbidity, impacting patient quality of life, and increasing healthcare costs. Identifying risk factors is essential for effective prevention and management. METHODS: This case-control study, conducted in the Department of General Surgery at a tertiary medical institute, included patients who underwent emergency laparotomy between 2019 and 2021. Those developing IH served as cases, and those not developing it as controls. Data on demographics, risk factors, and variables were collected and analyzed using SPSS V24, with significance set at p ≤ 0.05. RESULTS: Among 367 emergency laparotomies performed, 54 developed IH (incidence: 14.7%). Significant risk factors identified included obesity (p<0.000), smoking (p=0.036), COPD (p<0.001), diabetes mellitus (p=0.003), low hemoglobin (p=0.023), high total leukocyte count (p=0.001), low total protein (p=0.015), low albumin (p=0.002), and high creatinine (p=0.001). Operation-related factors such as increased operation time (p=0.001), increased blood loss (p=0.025), intraoperative blood transfusion (p=0.039), and peritoneal contamination (p=0.030) were significant. Mass closure of the abdomen significantly reduced the risk of IH (p=0.018). Postoperative factors like surgical site infection (p<0.001), wound dehiscence (p=0.001), postoperative straining (p=0.001), and prolonged hospital stay (p=0.000) were also significantly associated. DISCUSSION: The study underscores the multifactorial nature of IH development post-emergency laparotomy, identifying significant preoperative, intraoperative, and postoperative risk factors. The findings suggest that managing comorbidities, optimizing nutritional and inflammatory status, and implementing effective surgical and postoperative strategies are crucial in reducing IH incidence.